2017
DOI: 10.1177/0954406217694064
|View full text |Cite
|
Sign up to set email alerts
|

Deformation analysis and experiments for functional surface of composite antenna structure

Abstract: Composite structure with embedded microstrip antenna array is a multifunctional structure that can provide the capabilities of a panel skin structure and a radar antenna simultaneously, and it is usually installed in the structural surface of the air, water, and ground vehicles. The environmental load under in-service conditions leads to structural deformations of the composite antenna structure. In this paper, theoretical analysis and experimental validations were presented to investigate the deformations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The out of plane deformation plots for node path M1, M2, L1, L2, and D1 is shown in Figures 9,10,11, 12, and 13, respectively. From these plots, it has been observed that the out of place deformation in all node paths is significantly less for K2 reflector than K1 reflector.…”
Section: Effect On Membrane Wrinklingmentioning
confidence: 99%
See 1 more Smart Citation
“…The out of plane deformation plots for node path M1, M2, L1, L2, and D1 is shown in Figures 9,10,11, 12, and 13, respectively. From these plots, it has been observed that the out of place deformation in all node paths is significantly less for K2 reflector than K1 reflector.…”
Section: Effect On Membrane Wrinklingmentioning
confidence: 99%
“…[5][6][7][8][9] Most of the spacecraft systems are designed with mass and volume constraints; therefore, flexible, elastic, and membrane-based structures are increasing applications in spaceborne systems. [10][11][12] The membrane structures possess small thickness along with negligible bending and compressive strength. Therefore, such structures can be easily wrinkled and have low natural frequency of vibration.…”
Section: Introductionmentioning
confidence: 99%